Solutions of Unified Fractional Schrödinger Equations. (29th December 2011) - Chaurasia, V. B. L.; Kumar, Devendra
Abstract : We obtain the solution of a unified fractional Schrödinger equation. The solution is derived by the application of the Laplace and Fourier transforms in closed form in terms of the Mittag-Leffler function. The result obtained here is quite general in nature and capable of yielding a very large number of results (new and known) hitherto scattered in the literature. Most of results obtained are in a form suitable for numerical computation.